Aggregate demand, idle time, and unemployment - Pascal Michaillat; Emmanuel Saez (W.E. Upjohn Institute for Employment Research, 2014)
This paper develops a model of unemployment fluctuations. The model keeps the architecture of the Barro and Grossman (1971) general disequilibrium model but replaces the disequilibrium framework on the labor and product markets by a matching framework. On the product and labor markets, both price and tightness adjust to equalize supply and demand. There is one more variable than equilibrium condition on each market, so we consider various price mechanisms to close the model, from completely flexible to completely rigid. With some price rigidity, aggregate demand influences unemployment through a simple mechanism: higher aggregate demand raises the probability that firms find customers, which reduces idle time for firms' employees and thus increases labor demand, which in turn reduces unemployment. We use the comparative-statistics predictions of the model together with empirical measures of quantities and tightnesses to re-examine the origins of labor market fluctuations. We conclude that (1) price and real wage are not fully flexible because product and labor market tightness fluctuate significantly; (2) fluctuations are mostly caused by labor demand and not labor supply shocks because employment is positively correlated with labor market tightness; and (3) labor demand shocks mostly reflect aggregate demand and not technology shocks because output is positively correlated with product market tightness.
Keywords: E10; E24; E30; J2; J64; 330; aggregate demand; unemployment; matching frictions; business cycles